Two new species and additional records of mainland Chinese Domene (Coleoptera: Staphylinidae: Paederinae) - Lin, Xiao-Bin; Peng, Zhong (Zootaxa, 2021)
Material of the genus Domene Fauvel, 1873 from the Chinese provinces Heilongjiang, Gansu, Hunan, Guangdong, Guangxi, Sichuan and Guizhou is examined. Eight species were identified, six of them described previously and two are newly described: D. hui sp. n. (Guangdong: Shimentai); D. leigongensis sp. n. (Guizhou: Leigong Shan). The genus is now represented in mainland China by 23 species.